2008
DOI: 10.1111/j.1751-7141.2008.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Pharmacist‐Led Cardiovascular Risk Reduction Clinic for Diabetic Patients With and Without Mental Health Conditions

Abstract: Coexisting mental health conditions (MHCs) attenuate treatment effects in diabetes. A retrospective analysis was performed of a pharmacist‐led cardiovascular risk reduction clinic (CRRC) targeting hypertension, diabetes, hyperlipidemia, and tobacco use in patients with at least one CRRC visit between January 2001 and January 2002. The United Kingdom Prospective Diabetes Study (UKPDS) risk change (after/before CRRC) for those with and without MHCs was compared. Of the 297 with diabetes and complete UKPDS data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…[8][9][10] Clinical pharmacists at the Veterans Health Affairs have prescriptive authority to manage medication therapy under federal regulation, and there are data to support their effectiveness in the management of diabetes and cardiovascular risk factors in the individual clinic settings. 11,12 Pharmacists can also be trained to be diabetes educators and participate in diabetes self-management education programs. 13 However, it is unknown whether the use of clinical pharmacists in lieu of physicians in a group medical appointment program for the management of diabetes and associated cardiac risk factors is feasible or efficacious.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Clinical pharmacists at the Veterans Health Affairs have prescriptive authority to manage medication therapy under federal regulation, and there are data to support their effectiveness in the management of diabetes and cardiovascular risk factors in the individual clinic settings. 11,12 Pharmacists can also be trained to be diabetes educators and participate in diabetes self-management education programs. 13 However, it is unknown whether the use of clinical pharmacists in lieu of physicians in a group medical appointment program for the management of diabetes and associated cardiac risk factors is feasible or efficacious.…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that compared with standard care, adding pharmacists to the primary care team resulted in a median absolute reduction in the UKPDS risk score of 1.0% after 1 year. 22 The study described in this article also used the UKPDS risk engine but demonstrated even greater (i.e., up to 4.5-fold) reductions in the estimated 10-year Am J Health-Syst Pharm-Vol 70 May 15, 2013 of enhanced versus usual care might have been even greater.…”
Section: Type Of Effectmentioning
confidence: 93%
“…Pharmacists at VA medical centers assessed diet at baseline and developed action plans that included referral to nutritionists as part of an individualized program. 23 A community pharmacy study also incorporated lifestyle changes. Patients with uncontrolled hypertension were enrolled at nine community pharmacies in the same region and chain.…”
Section: Diet and Dietary Sodium Counselingmentioning
confidence: 99%